Seasonal variations in public perceptions of diphtheria in Northern Nigeria - Abara Erim; Habibat Ohunene Lawal; Chizaram Anselm Onyeaghala; Chinenye Claire Chukwu-Mba; Olufunke Olayemi Ajibade; Ukamaka Gladys Okafor; Okechi Eberechukwu Nzedibe (BMC Public Health)
Abstract Background Diphtheria remains a significant public health concern in Nigeria, with over 20,000 suspected cases and more than 500 deaths reported during the 2022–2023 outbreak period, particularly concentrated in the northern regions. Understanding public perceptions and behavior regarding diphtheria, including symptoms, transmission, and vaccination across different seasons, is vital for developing effective interventions. This study aimed to evaluate seasonal variations in public awareness of diphtheria, including knowledge of its symptoms and information sources. Additionally, it sought to assess the perceived at-risk groups and attitudes toward diphtheria vaccination in the country. Methods A cross-sectional survey was conducted among residents aged 18 years and older in Kano, Katsina, Bauchi, Yobe, Borno, Kaduna, Jigawa, Kebbi, and the Federal Capital Territory (FCT). Data were collected by trained fieldworkers over 12 months via structured questionnaires divided into four sections: demographics, public awareness, perceived risk, and vaccination attitudes. Ethical approval was obtained, and verbal informed consent was secured from all participants. Data analysis involved descriptive statistics and statistical tests to examine associations between variables. Results A total of 3,070 respondents participated in the study. Public awareness of common diphtheria symptoms such as fever (68.0%) and sore throat (60.5%) was high, whereas awareness of conjunctivitis (23.9%) was lower. Children under 5 years of age were consistently perceived as the most at-risk group (80.5%). The willingness to vaccinate against diphtheria remained high at 94.4%, with no significant seasonal variation (p-value 0.894; Chi-square test). Radio (53.1%) was identified as the primary information source, especially during the rainy season (54.6%). Seasonal variations in preventive and vaccination practices were minimal, indicating consistent public health behaviors throughout the year. Conclusion This study highlights the importance of maintaining robust public health education campaigns, leveraging both traditional and digital media to sustain high awareness and vaccination rates for public health interventions. Based on our findings, we recommend implementing targeted school-based health education programs and strengthening partnerships with community health workers to enhance diphtheria awareness, especially among caregivers of young children. Understanding sociodemographic and seasonal contexts is crucial for effective public health interventions, ensuring that at-risk groups are adequately protected.